Association of Household Food Safety Practices with Stunting in Children Under Five: A Case-Control Study in A High-Prevalence Indonesian Village - Habibi, Nur Ahmad; Ariska, Neza Viona; Ismanilda, Ismanilda; Zulkifli, Zulkifli; Handayani, Marni; Utami, Citra Tristi (Journal of Health and Nutrition Research, 2025)
One of the factor’s causing stunting is infection related to poor household food safety practices. This study aims to analyze the correlation between household food safety practices and the incidence of stunting in Sibakur Village, Sijunjung District, Indonesia. The research used a case-control design with a sample size of 60 toddlers (30 cases and 30 controls) selected by simple random sampling. Data were collected through interviews using a questionnaire and analyzed by chi-square test, calculation of odds ratio (OR) with Confidence Interval (CI). The results showed a significant relationship between food safety practices and the incidence of stunting (p = 0.000; OR = 8.5; 95% CI =2.3-30.4), which means that toddlers from households with poor food safety practices have an 8.5 times higher risk of being stunting. Food safety factors closely related to stunting include sanitation, personal hygiene, raw materials, pest control, and cross-contamination. In conclusion, poor household food safety practices significantly increase the risk of stunting. Therefore, educative interventions of food safety need to be strengthened as a strategy to prevent stunting at the household level.